The Scientific Rationality of the Hadith on Habbah al-Saudā’: An Analysis of Its Meaning and Relevance to Modern Chemistry - Fitri Nova Anggriana; Ibnu Hajar Ansori; Baroud Najah (LPPM UIN Syekh Wasil Kediri, 2026)
The Prophetic tradition regarding Habbah al-Saudā’ (Nigella sativa L.), often translated as “black cumin,” describes it as “a cure for every disease.” This statement has frequently been interpreted in a purely literal and theological sense, neglecting its scientific and contextual dimensions. Such interpretation creates a significant gap between classical religious understanding and the paradigm of modern chemistry, which emphasizes molecular interactions, biochemical mechanisms, and compound specificity in pharmacological activity. This study adopts a library research approach combined with contextual and scientific interpretation to reexamine the hadith text alongside empirical data from contemporary chemical and pharmaceutical studies. The findings demonstrate that Habbah al-Saudā’ contains over one hundred bioactive compounds, with thymoquinone (C₁₀H₁₂O₂) and nigellone (C₁₈H₂₂O₄) as the most dominant constituents. These compounds exhibit antioxidant, anti-inflammatory, antimicrobial, and immunomodulatory properties that support the body’s immune system and maintain homeostatic balance. Rather than serving as a universal cure, the hadith can thus be interpreted as promoting preventive health and physiological resilience through natural bioactive substances. This research contributes to the epistemological integration between revelation and modern science by providing a rational-scientific framework for understanding Prophetic medicine. It also opens new avenues for interdisciplinary studies exploring the molecular pharmacology of prophetic remedies, thereby reinforcing the relevance of Islamic medical traditions within the contemporary discourse of chemical sciences.